Cocoa (Theobroma cacao): An overview of current research on botanical, phytochemical and pharmacological aspects (Research, Society and Development, 2024)
Objectives: To highlight phytochemical compounds present in cocoa and correlate them with the pharmacological activities of the plant species. Due to its wide use and its therapeutic potential, this species was investigated, producing data that were organized and arranged in this review, in order to provide an overview of different aspects of Theobroma cacao. Methodology: It consists of an integrative literature review to analyze articles published between 2014 and 2024 found in the virtual databases: National Library of Medicine (PubMed), ScienceDirect, Scientific Electronic Library Online (SciELO) and Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) using the descriptors in English and Portuguese: “Theobroma cacao, Traditional use, Botany, Chemical composition, Pharmacological activity'' and their combinations, refining the findings with the Boolean operator AND and OR. Results: During the initial search period, 2,887 articles were found, 123 of these publications being potentially eligible according to the inclusion and exclusion criteria adopted in the journal. After reading the abstracts, 35 remained and of these, only 4 articles were selected for analysis. Therefore, the articles showed that the T. cacao species is rich in polyphenols and methylxanthines, which have antimicrobial, antioxidant and cognitive capabilities. Thus, understanding these aspects may open new perspectives for the development of dietary and pharmacological interventions aimed at preventing or treating neurodegenerative disorders and improving overall quality of life.